Intensity-modulated radiation therapy as adjuvant treatment for local advanced malignant mesothelioma after pleuropneumonectomy – report of two cases - Kowalski, Dariusz M.; Winiarczyk, Kinga; Knetki-Wróblewska, Magdalena; Krzakowski, Maciej; Orłowski, Tadeusz; Zajda, Katarzyna; Garmol, Dariusz; Jaśkiewicz, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Malignant pleural mesothelioma is a malignancy with bad prognosis. The cause of treatment failure is local recurrence and dissemination. As seen, multidisciplinary procedures can bring correction of results of treatment including thoracic surgery, systemic treatment (chemotherapy) and radiation. The paper presents two cases with advanced malignant pleural mesothelioma after radical pleuropneumonectomy and adjuvant irradiation (intensity-modulated radiation therapy, IMRT) due to R1 attribute.